2018
DOI: 10.12788/ajo.2018.0063
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Reduces Perioperative Blood Loss and Hemarthrosis in Total Ankle Arthroplasty

Abstract: Tranexamic acid (TXA) is an effective agent used for reducing perioperative blood loss and decreasing the potential for postoperative hemarthrosis. We hypothesized that patients who had received intraoperative TXA during total ankle arthroplasty (TAA) would have a reduction in postoperative drain output, thereby resulting in a reduced risk of postoperative hemarthrosis and lower wound complication rates. A retrospective review was conducted on 50 consecutive patients, 25 receiving TXA (TXA-TAA) and 25 not rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…In a retrospective review of 50 patients undergoing TAR, 25 patients who received intraoperative IV TXA had a significantly lower drain output (71.6 mL vs 200.2, P < .0001) and change in pre-to postoperative hemoglobin level (0.4 vs 1.5 g/dL, P ¼ .01) compared to the 25 patients who did not receive intraoperative TXA. 25 Additionally, there was a lower wound complication rate (8% vs 20%, P ¼ .114) in patients treated with TXA vs nontreated patients; however, this was not statistically significant. 25 In a randomized controlled trial comparing outcomes after TXA vs non-TXA treatment for 90 consecutive calcaneal fractures, the TXA-treated cohort had a significantly reduced incidence of wound complications (7.3% vs 23.8%, P ¼ .036) without a significant difference in thromboembolic events or adverse drug reactions between the 2 groups.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a retrospective review of 50 patients undergoing TAR, 25 patients who received intraoperative IV TXA had a significantly lower drain output (71.6 mL vs 200.2, P < .0001) and change in pre-to postoperative hemoglobin level (0.4 vs 1.5 g/dL, P ¼ .01) compared to the 25 patients who did not receive intraoperative TXA. 25 Additionally, there was a lower wound complication rate (8% vs 20%, P ¼ .114) in patients treated with TXA vs nontreated patients; however, this was not statistically significant. 25 In a randomized controlled trial comparing outcomes after TXA vs non-TXA treatment for 90 consecutive calcaneal fractures, the TXA-treated cohort had a significantly reduced incidence of wound complications (7.3% vs 23.8%, P ¼ .036) without a significant difference in thromboembolic events or adverse drug reactions between the 2 groups.…”
Section: Discussionmentioning
confidence: 86%
“…25 Additionally, there was a lower wound complication rate (8% vs 20%, P ¼ .114) in patients treated with TXA vs nontreated patients; however, this was not statistically significant. 25 In a randomized controlled trial comparing outcomes after TXA vs non-TXA treatment for 90 consecutive calcaneal fractures, the TXA-treated cohort had a significantly reduced incidence of wound complications (7.3% vs 23.8%, P ¼ .036) without a significant difference in thromboembolic events or adverse drug reactions between the 2 groups.…”
Section: Discussionmentioning
confidence: 86%
“…4,7,8,18,20,22 Despite the extensive literature investigating TXA use in total knee and total hip arthroplasty, there is a paucity of literature involving the use of TXA in TAA. In a recent study, Nodzo et al 13 retrospectively evaluated the use of TXA in total ankle arthroplasty. They found that TXA use decreased perioperative blood loss, hemarthrosis, and wound complications compared with patients who did not receive TXA.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8,18,20,22 There has been a paucity of literature investigating TXA use in foot and ankle surgery. In a recent article, Nodzo et al 13 showed, in a retrospective study, that TXA use in total ankle arthroplasty resulted in decreased perioperative blood loss, hemarthrosis, and wound complications when compared with patients who did not receive TXA. In another study evaluating surgery about the foot and ankle, Xie et al 21 showed that TXA reduced the postoperative blood loss wound complication rate with no reported complications.…”
Section: Introductionmentioning
confidence: 99%
“…These authors concluded that TXA may be an effective, cost-efficient, hemostatic agent when used during total ankle arthroplasty and reliably can reduce perioperative blood loss, hemarthrosis, and the risk of wound complications. 26 The utility of TXA has also been studied in the context of calcaneus fractures. Specifically, a 2015 randomized controlled trial by Xie et al was undertaken to evaluate the effect of TXA in reducing postoperative blood loss in calcaneal fractures.…”
Section: Tranexamic Acid In Foot and Ankle Surgerymentioning
confidence: 99%